Assessment of Reference Values for Copper and Zinc in Blood Serum of First and Second Lactating Dairy Cows. (15th March 2010) - Spolders, Markus; Höltershinken, Martin; Meyer, Ulrich; Rehage, Jürgen; Flachowsky, Gerhard
Abstract : The influence of different copper and zinc contents in rations on blood serum concentrations in dependence on feeding (Groups A and B) and lactation (Lactation 1 and 2) was tested in a feeding trial with 60 German Holstein cows. All animals received a diet based on maize and grass silage ad libitum. 30 cows received a concentrate supplemented with copper and zinc as recommended (Group A), whereas the other 30 animals were offered a concentrate with roughly double the amount of copper and zinc (Group B). Blood samples were taken several times during the lactation to analyse serum concentrations of copper and zinc. Copper serum concentration was influenced neither by the different feeding (11.7 μ mol/L in Group A and 12.3 μ mol/L in Group B) nor by the lactation (12.0 μ mol/L in Lactation 1 and 12.1 μ mol/L in Lactation 2). Zinc serum concentration was significantly influenced as well as by feeding (14.1 μ mol/L in Group B and 12.5 μ mol/L in Group A) and lactation (14.2 μ mol/L in the second lactation and 12.8 μ mol/L for first lactating cows). For an exact diagnosis of trace element supply, blood serum is a not qualified indicator; other sources (feedstuffs, liver, hair) must also be investigated.